PERTUMBUHAN DAN HASIL TANAMAN OKRA (Abelmoschus esculentus) YANG DIBERI BOKASHI KAYAMBANG (Salvinia molesta) DAN PUPUK FOSFOR PADA TANAH GAMBUT PEDALAMAN (Growth and Yield of Okra (Abelmoschus esculentus) by Applying of Bokashi Kayambang (Salvinia molesta) and Phosphorus Fertilizer on Peat Soil) - iat, R, Af; narti, S., Wi; hid, A, Sya (AGRIPEAT, 2017)
ABSTRACTThis study aimed to determine the effect of bokashi kayambang (Salvinia molesta) and Phosphorus Fertilizer on Peat Soil on growth and yield of okra (Abelmoschus esculentus). This study was conducted in October 2012-March 2013 at Jl. Lais II, Bukit Tunggal, Jekan Raya, Palangka Raya. This study used a completely randomized design (CRD) with two factor factorial treatment. The first factor was Applying of Bokashi Kayambang(K) consisting of 5 levels, namely: K0 = 0 t.ha-1, K1 = 2,5 t.ha-1, K2 = 5,0 t.ha-1, K3 = 7,5 t.ha-1, K4 = 10 t.ha-1. The second factor was the provision of phosporus fertilizer (P) which consist of 5 levels, namely: P0 = 0 kg.ha-1, P1 = 150 kg.ha-1, P2 = 200 kg.ha-1, P3 = 250 kg.ha-1, P4 = 300 kg.ha-1, so there are 25 combinations of treatment and repeated three times so that there are 75 units experiment. The result showed that interaction of bokashi kayambang dose 2,5 t.ha-1 and without phosphorus fertilizer were giving the best effect for the average of plant height at the age of 1 WAP. The interaction of bokashi kayambang dose 2,5 t.ha-1 and phosphorus fertilizer 300 kg.ha-1 were giving the best effect for the average of plant height at the age of 6 WAP.The single treatment of bokashi kayambang dose 2,5 t.ha-1was the best effect for the average of plant height at the age 5 WAP and harvest weight. The single treatment of phosphorus fertilizer dose 300 kg.ha-1was the best effect for the harvest weight .Keywords: okra, bokashi kayambang, phosporus, peat soil.